Involvement of the N-terminus of Kir6.2 in the inhibition of the KATP channel by ATP. - Proks, P; Gribble, F; Adhikari, R; Tucker, S; Ashcroft, F (1999)
1. ATP-sensitive potassium (KATP) channels are composed of pore-forming Kir6.2 and regulatory SUR subunits. A truncated isoform of Kir6.2, Kir6.2DeltaC26, expresses ATP-sensitive channels in the absence of SUR1, suggesting the ATP-inhibitory site lies on the Kir6. 2 subunit. 2. We examined the effect on the channel ATP sensitivity of mutating the arginine residue at position 50 (R50) in the N-terminus of Kir6.2, by recording macroscopic currents in membrane patches excised from Xenopus oocytes expressing wild-type or mutant Kir6.2DeltaC26. 3. Substitution of R50 by serine, alanine or glycine reduced the Ki for ATP inhibition from 117 microM to 800 microM, 1.1 mM and 3.8 mM, respectively. The single-channel conductance and kinetics were unaffected by any of these mutations. Mutation to glutamate, lysine, asparagine, glutamine or leucine had a smaller effect (Ki, approximately 300-400 microM). The results indicate that the side chain of the arginine residue at position 50 is unlikely to contribute directly to the binding site for ATP, and suggest it may affect ATP inhibition by allosteric interactions. 4. Mutation of the isoleucine residue at position 49 to glycine (I49G) reduced the channel ATP sensitivity, while the mutation of the glutamate residue at position 51 to glycine (E51G) did not. 5. When a mutation in the N-terminus of Kir6.2DeltaC26 that alters ATP sensitivity (R50S; Ki, 800 microM) was combined with one in the C-terminus (E179Q; Ki, 300 microM), the Ki for the apparent ATP sensitivity was increased to 2.8 mM. The Hill coefficient was also increased. This suggests that the N- and C-termini of Kir6.2 may co-operate to influence channel closure by ATP.